Two new species in Hieracium sect. Alpestria (Asteraceae) from Mt. Babia Góra, Western Carpathians, Poland - Szeląg, Zbigniew (Phytotaxa, 2024)
Two apomictic, tetraploid (x=9) species in Hieracium sect. Alpestria are described from Mt. Babia Góra, the northernmost mountain massif in the whole Carpathian chain with an alpine belt. Hieracium babiogorense combines the morphological features of H. prenanthoides s.lat. and H. bifidum s.lat., and H. besseri is of presumably hybrid origin between H. prenanthoides s.lat. and H. caesium s.lat. Both new species are illustrated with photos of the holotypes and live plants in the type localities.